KONTRIBUSI PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA KARYAWAN GENERASI MILLENNIAL - Felicia Leonardi; Suryadi Tandiayuk; Sri Wahyuni (Jurnal Psikologi Poseidon, 2023)
The workplace is dominated by millennial workers, and this trend is expected to continue. Although millennial workers are capable of doing their jobs quickly, intelligently, and effectively, corporate citizenship behavior among millennial workers is still underdeveloped. Perceived organizational support is one of the variables that affects organizational citizenship behavior. The purpose of this research is to ascertain how millennial workers in Makassar City's organizational citizenship behavior is influenced by perceived organizational support. The quantitative method and correlational research design are both used in this work. There were 230 participants in this research, all of whom worked as millennials in Makassar city. The Organizational Citizenship Behavior Scale (OCBS) and the Survey of Perceived Corporate Support were used to measure outcomes (SPOS). These findings of this study show that perceived organizational support makes a major contribution to organizational citizenship behavior in millennial employees at Makassar City by 28,8%